Transmission of HBV in patients with acute Hepatitis in Babol, 1996-98 - MR Hassanjani Roshan (Babol University of Medical Sciences, 1999)
Objective: Hepatitis B is one of the most important problems in the world and each year a large number of people die from acute and chronic sequelae of HBV. The most important routes of transmission in the developed countries are sexual and intravenous injection in drug abusers, but in our country the modes of transmission are unknown. The aim of this study was determination of possible routes of transmission in patients who were admitted to infectious unit of Babol Yahyanejad hospital during 1996-1998. Methods: This descriptive study was conducted on acute hepatitis B patients. The following variables were evaluated in all patients: Age, sex, occupation, infection in other family members and a history of sexual contact, blood transfusion, surgery or any dental procedure during the past 6 months. Findings: 134 cases were studied. 79 (59%) were male and 55 (41%) female. The mean age ±SD was 31±15.5 years. Most of the patients were at their third decade of life and 80.5% were between 10-49 years old. The routes of transmission were determined in 83 cases (63%). Family contact with HBV infection was 42.5%, history of surgery and dental procedure 9.8%, blood transfusion 6%, sexual contact 1.5% and medical staff were 2.2%. Conclusion: The results of this study show that the routes of transmission of HBV in our society probably differ from developed countries, so we recommend all family members of patients should be checked, and the susceptible ones must be vaccinated. Medical and dental equipment must be sterilized and central sterile unit personnel should be trained precisely. Sensitive screening tests are highly recommended in blood banks to reduce post-transfusion hepatitis B.